Armies of Peace : Canada and the UNRRA Years - Armstrong-Reid, Susan, 1950- (Book collections on Project MUSE., 2008)
Armies of Peace is the first comprehensive investigation of Canadians' influence on the establishment and operation of The United Nations Relief and Rehabilitation Administration (UNRRA).